It Is Time to Talk About Visa Fraud. Again. - Goodman, Allan (International Higher Education, 2025)
<h3 id="visa-fraud-has-been-a-serious-problem-in-international-student-recruitment-for-many-decades-already-the-increase-in-international-student-mobility-and-the-use-of-agents-and-new-technologies-exacerbate-the-problem-and-require-joint-actions-to-combat-this-fraud-in-the-interest-of-ethical-policies-for-international-student-recruitment-in-the-united-states-and-elsewhere" data-pm-slice="1 1 []">Visa fraud has been a serious problem in international student recruitment for many decades already. The increase in international student mobility and the use of agents and new technologies exacerbate the problem and require joint actions to combat this fraud in the interest of ethical policies for international student recruitment, in the United States and elsewhere.